Strategic career behaviours among hybrid workers: testing a general European model - Hildred, Kiall; Piteira, Margarida; Cervai, Sara; Pinto, Joana Carneiro (Frontiers in Psychology, 2024)
This study investigates the antecedents and consequences of strategic career management behaviours in a sample of European hybrid workers. A total of 739 employees (Male=442, 59.8%) with a mean age of 27.64 years (SD=8.48; Range=[18, 70]), working mostly full-time (n=398, 53.9%) and with 46.35% of their work being done hybrid-like participated in this study. The study tested perceived self-efficacy, desire for career control and perceived organizational support as predictors of strategic career behaviours. And tested strategic career behaviours as predictors of perceived career control, objective and subjective career success, and career satisfaction. Results indicate objective career success was not related to the antecedent variables of strategic career behaviours and hence was removed from the model. Regression and mediation analyses demonstrated that perceived self-efficacy and desire for career control are good predictors of the use of strategic career behaviours, but perceived organizational support is not; strategic career behaviours are reasonable predictors of perceived control, and very strong predictors of subjective career success and career satisfaction. These results will support career management programs, accounting for idiosyncrasies of hybrid work.